Identification of Competence Contribution on Higher Education - Junianti, Emmy; Reza, Bobby (Journal Corner of Education, Linguistics, and Literature, 2024)
The identification of job competency contributions in higher education is crucial for optimizing talent development and institutional performance. This study aims to identify job competency requirements (JCR) as a fundamental instrument in talent development and establish appropriate methods for measuring JCR for non-lecturer positions in higher education institutions. Using a quantitative research approach, data were collected through surveys to analyze competency requirements effectively. A case study was conducted at a university in Indonesia with an institutional accreditation rating of A (Superior), ensuring a high standard of academic and administrative operations. The findings of this study contribute to the development of a competency-based framework that supports human resource management, career development, and organizational effectiveness within higher education institutions. The results are expected to provide strategic insights into improving workforce capabilities, aligning institutional goals with employee competencies, and enhancing overall institutional performance.